Adipose stem cell-derived exosomes circular RNA circFryl attenuate atrial fibrosis and cardiomyocyte apoptosis in atrial fibrillation - Chunpu Li; Jiuting Tan; Xintao Deng (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Atrial fibrillation (AF) is a prevalent arrhythmia accompanied by structural and electrical remodeling of the heart. Here, we examined the possible mechanisms behind the protective role of adipose-derived stem cell (ADSC)-derived exosomes in AF therapy.Materials and Methods: We isolated exosomes from ADSCs. Exosome treatment was given. The left atrial diameter was measured by echocardiographic imaging. Cardiac fibrosis and damage were detected. The interaction between miR-338-3p with circFryl and tissue inhibitor of metalloproteinase mRNA (4TIMP4 mRNA) was predicted and investigated using qPCR and western blotting assay. Results: The overexpression of circFryl in ADSCs elevated the level of circFryl in exosomes and the myocytes, whereas knockdown of circFryl exhibited the opposite effects. Treatment with ADSC-exosomes significantly elevated circFryl level and recovered left atrial diameter, whereas knockdown of circFryl in exosomes abolished these effects. ADSC-exosomes alleviated the cardiac fibrosis and cell apoptosis in the AF model, and the knockdown of circFryl abolished these effects. ADSC-exosomes treatment suppressed viability and fibrosis and enhanced cell apoptosis in Ang-II-induced fibroblasts, which was reversed by depletion of circFryl. Online analysis of miRNA interaction targets showed potential binding between miR-338-3p with circFryl and TIMP4 mRNA. Knockdown of circFryl notably suppressed TIMP4 level, and inhibition of miR-338-3p recovered TIMP4 level. TIMP4 overexpression and miR-338-3p inhibition abolished the effects of sicircFryl in vitro and in vivo.  Conclusion: The ADSC-derived exosomes delivered circFryl to interact with miR-338-3p, subsequently enhancing TIMP4 mRNA stability and expression in cardiac fibroblasts and myocytes. The circFryl/miR-338-3p/TIMP4 axis mediated the protective effects of ADSC on AF.